Pathogenicity of avian reovirus variant in the immune organs of broiler chicks - Haiyang Yu; Yudong Zhu; Qiong Wu; Wanjun Zhao; You Wang; Dong Wang; Huaguang Lu; Youxiang Diao; Yijing Li; Yi Tang (Virus Research)
In recent years, the infection rate of avian reovirus (ARV) in chicks has been continuously increasing, seriously endangering the healthy development of China's chicken farming industry. However, the pathogenicity of this virus in immune organs has been less studied. In this study, an ARV strain (Chicken/XJ/China/2022/01/16) was isolated from arthritic broiler chicks in Xinjiang province and whole genome sequencing of the ARV strain was performed using next generation sequencing (NGS) technology, and sequence analysis showed that the strain was a type V variant of the ARV gene. In order to further understand the pathogenicity of this strain in terms of immune organs, we randomized 120 healthy 1-day-old broilers equally into 3 groups (oral, footpad inoculation and control), where 2 experimental groups were inoculated with 0.2 mL of ARV (TCID50 of 105.5 /0.1 mL) and the control group was inoculated with an equal amount of sterile saline. The results showed that the footpad inoculation group showed more severe symptoms, which, in addition to causing chick dwarf syndrome and viral arthritis, would also cause serious effects on the immune organs of the chicks. Among them, the spleen and bursa were most seriously damaged, the symptoms of arthritis appeared relatively late, which indicated that the spleen and bursa might be the main target organs preferentially attacked by avian reovirus. This study provides a rationale for the prevention and control of emerging avian reovirus and adds to the evidence of the effects of ARV on immune organs, with the expectation that it will be useful in understanding the immune response-related aspects of the disease in subsequent studies.